"An eye for form" : epigraphic essays in honor of Frank Moore Cross - Hackett, Jo Ann; Aufrecht, Walter Emanuel, 1942-; Amadasi, Maria Giulia (Eisenbrauns, 2014)
At the first meeting of his class in Northwest Semitic Epigraphy at Harvard, Frank Cross would inform students that one of the things each of them needed was an "eye for form." By this, he meant the ability to recognize typological or evolutionary change in letters and scripts. Frank, like his teacher William Foxwell Albright, was a master of typological method. In fact, typology was the dominant feature of his epigraphic work, from the origins of the alphabet to the development of the scripts of the Dead Sea Scrolls. Indeed, he has written about the importance of typology itself. Because Frank Cross has so dominated the study of the ancient Near East in the last 60 years, Aufrecht once asked him what he considered his primary field of study to be. Without hesitation, he said, "Epigraphy." It seems, therefore, that the field that he loved and to which he contributed so much is an appropriate subject for this Festschrift in his honor, which is being presented by his colleagues, friends, and former students. Included are an appreciation by Peter Machinist and a contribution by the late Pierre Bordreuil.